Feeding the Debate: A Qualitative Framing Analysis of Organic Food News Media Coverage - Courtney Meyers; Katie Abrams (Journal of Applied Communications, 2010)
Consumer interest in organic food has increased in recent years due to concerns over conventional production practices, health standards and environmental protection. Organic food production can be viewed as both an ally and rival of traditional agriculture. Americans tend to be more susceptible to media coverage about production agriculture. Determining how the media frames organic food is important because news frames can determine what becomes salient in conversations from the dinner table to Capitol Hill. This study employed qualitative content analysis methodology to discover how five national newspapers framed organic foods during an 18-month period. Emergent frames included “ethical,” “health,” “production,” and “industrialization.” Emphasis was placed on the ethical and moral reasons to purchase organic food with limited discussion of the scientific evidence for consumer claims of superior quality, safety, and nutrition. Overall, common sources included consumers, industry representatives, and organic farmers. Future research should utilize the identified frames to examine news coverage over a longer time frame and in additional media such as agricultural magazines.
Keywords: Consumer; industrialization; ethical and moral reasons; magazines; Media Coverage; organic and natural food